KEMAMPUAN BERPIKIR KREATIF MELALUI MODEL PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA DALAM PEMECAHAN MASALAH SISWA SMP - Saiful Bahri, Samsul Bahri, Alkausar Saragih, Bambang Hermanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The purpose of this study is to determine the ethnomathematics-based learning problem model to see the creative thinking and problem-solving abilities of students of SMP Negeri 23 Medan on the material of flat shapes. The number of samples in this study were 25 students of grade IX of SMP Negeri 23 Medan, Binjai Village, Medan Denai District, Medan City, North Sumatra Province. This study is an experimental study with the Group Pretest-postest design. The subjects in this study were students of grade IX of SMP Negeri 23 Medan, Binjai Village, Medan Denai District, Medan City, North Sumatra Province. Data collection used ethnomathematics creative thinking ability tests in improving problem-solving abilities. The data analysis technique used in this study was the paired t-test. The results of this study are 1) the results of the paired sample t-test show the value of t count < t table or 7.575 < 2.19302 then H0 is rejected which means that students' creative thinking abilities through the ethnomathematics Problem Based Learning model in improving Problem Solving and Creative Thinking Ability on flat shape material, 2) the results of the average increase test (N-gain) show that grade IX students of SMP Negeri 23, namely 56.25, are included in the medium category. The average pretest of students is 83.42 and the average posttest is 89.05. So it can be concluded that there is an increase in creative thinking abilities through the ethnomathematics problem based learning model in improving Problem Solving Ability on flat shape material at SMP Negeri 23 Medan, Binjai Village, Medan Denai District, Medan City, North Sumatra Provinc